The Role of Iron Chelation Therapy in Colorectal Cancer: A Systematic Review on Its Mechanisms and Therapeutic Potential - Gihani Vidanapathirana; Md Sajedul Islam; Sujani Gamage; Alfred K. Lam; Vinod Gopalan (Cancer Medicine)
ABSTRACT Background Despite significant therapeutic advancements in recent decades, colorectal cancer (CRC) continues to exhibit high rates of mortality and morbidity. Chemoresistance and cancer recurrence remain substantial challenges, underscoring the need for novel treatment approaches. Iron chelation therapy has gained profound interest over the years as a potential cancer treatment, leveraging the increased iron demand by tumors. This review evaluates the effects of iron chelation therapy on CRC progression and the underlying mechanisms. Method A comprehensive review of in vivo and in vitro studies was conducted to assess the effectiveness of iron chelation therapy in CRC. The literature search covered PubMed, Scopus, Medline (via Web of Science), and EMBASE between January 1995 and March 2024. Results Several in vitro and in vivo studies have investigated the impact of iron chelators, such as deferoxamine, deferasirox, thiosemicarbazone‐based chelators, quilamine‐based chelators, and other novel compounds on CRC. Natural plant extracts with iron‐chelating properties have also been explored as potential treatments. Most studies indicate that iron chelation can inhibit the proliferation of colon cancer cells, though some studies suggest cancer‐promoting effects. Mechanistically, iron chelation affects several hallmarks of CRC by modulating histone methylation, upregulating NDRG1, and influencing the Wnt/β‐catenin and p53 signaling pathways. However, certain iron chelators may inhibit TRAIL‐mediated apoptosis and activate the hypoxia‐inducible factor (HIF), potentially accelerating CRC progression. Conclusion Future exploration of iron chelation therapy in CRC should focus on extensive in vitro, in vivo, and clinical studies to elucidate the precise mechanisms involved. A deeper understanding of the genetic and cellular alterations induced by iron chelation will enhance the development of effective therapeutic strategies for CRC.